Triiodothyronin, Thyroxine and Thyrotropin in Vitiligo - Subba, K; Karn, D; Khatri, R (Kathmandu University Medical Journal, 2012)
Background Vitiligo is a common pigmentary disorder of the skin, affecting individuals globally. Not only is this ailment psychologically incapacitating, it also has a high incidence of autoimmunity, signifying that its manifestations may be the portrayal of dysfunction of immune system. Objective The aim of this study is to find out the situations of abnormal thyroid function test (TFT) in vitiligo patients. Methods A prospective cross sectional study was conducted at the Dhulikhel Hospital, KUTH, Dhulikhel during November 2008 to January 2011 with the objective to assess the thyroid function tests in vitiligo patients. Results Total 66 vitiligo patients with male 30 (45%) and female 36 (55%). Total 26 (39.39%) vitiligo patients have been found to have abnormal thyroid function test. Among them 10 had abnormal T3, seven had abnormal T4 and 12 had abnormal TSH level. Thyroid function test were normal in other vitiligo patients. Total seven vitiligo had high level of T3 than normal value, four male and three female. Two had higher level of T4 above 2.0 ng/dl and all were male, while five had abnormally low level of T4 with three male and two female. There were seven vitiligo patient with increased T3 level and three with decreased T3 level, among them six were males and four were females, the age group was ranged from seven to 68 years old. The T4 level were found abnormal in seven vitiligo patients among which five were males and two were females with the age group ranging from 7 to 51 years. Conclusions There has been significant association of thyroid disorder in the patient with vitiligo. Therefore, patient with vitiligo need to undergo thyroid function test to rule out the thyroid disorder and prevent from long-term complications. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6279 Kathmandu Univ Med J 2011;9(2):7-10